Bioassay for detection of xenobiotics - Abd. Shukor, Mohd. Yunus; Syed, Mohd. Arif; Halmi, Mohd. Izuan Effendi; Wan Johari, Wan Lutfi; Ahmad, Syahida; Abdul Rachman, Abdul Rahim (2014)
The present invention relates to bioassay for the detection of xenobiotics. The present invention also relates to a product for detection of xenobiotics based on the inhibition of luminescence of Photobacterium sp. strain MIE or a mutant thereof in an aqueous medium. Advantageously, the present invention contributes to improvement of bioassay for the detection of xenobiotics particularly for application in tropical country.